Poor Sleep Quality and Mood Disorders: Risk Factors of Increasing Chronic Pain in Patients with Insomnia - Liu L; Zhao X; Zhang X; Ren J; Zeng S; Dai Y; Zhang W; Zhou J (Nature and Science of Sleep, 2025)
Liu Liu,1,2,* Xianchao Zhao,3,* Xinyan Zhang,4 Jiafeng Ren,4 Si Zeng,2 Yuee Dai,2 Wensheng Zhang,1,5 Junying Zhou4 1Department of Anesthesiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Department of Anesthesiology, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 3Department of Neurology, Tangdu Hospital, Fourth Military Medical University, Xi’ an, People’s Republic of China; 4Sleep Medicine Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 5Laboratory of Anesthesia and Critical Care Medicine, National-Local Joint Engineering Research Centre of Translational Medicine of Anesthesiology, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wensheng Zhang, Department of Anesthesiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China, Email zhang_ws@scu.edu.cn Junying Zhou, Sleep Medicine Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China, Email zhoujy2016@scu.edu.cnObjective: The aim of this study was to examine the prevalence of chronic pain and its risk factors in patients with insomnia.Methods: We consecutively enrolled patients with chronic insomnia from Sleep Medicine Center in West China Hospital between May 2019 and February 2021. All patients were divided into two groups according to comorbid chronic pain or not. We used subjective questionnaires to assess sleep, daytime sleepiness, mood symptoms, and the characteristics and intensity of pain. Objective sleep quality was measured by polysomnography. The logistic regression analyses were used to identify the risk factors of chronic pain.Results: Among 358 patients with chronic insomnia, 48.9% had chronic pain. These patients had significantly higher scores in Hamilton Rating Scale for Anxiety (HAMA), Hamilton Rating Scale for Depression (HAMD), Visual Analog Scale (VAS) and Short-Form McGill Pain Questionnaire (SF-MPQ) (all PS < 0.001) compared to those without chronic pain. After controlling for the confounding factors, higher HAMA scores adjusted odds ratio = 1.083, 95% CI 1.033– 1.135, P = 0.001), higher HAMD scores (adjusted odds ratio = 1.109, 95% CI 1.058– 1.163, P < 0.001) and shorter N3 sleep duration (adjusted odds ratio = 0.969, 95% CI 0.940– 0.999, P = 0.041) were significantly associated with an increased risk of chronic pain. Multiple linear regression analyses showed that higher scores in Pittsburgh Sleep Quality Index (PSQI) (β = 0.108, 95% CI 0.026– 0.191, P = 0.010), HAMA (β = 0.085, 95% CI 0.043– 0.127, P < 0.001) and HAMD (β = 0.141, 95% CI 0.093– 0.188, P < 0.001) were positively related to pain intensity.Conclusion: Nearly half of patients with insomnia are comorbid with chronic pain. Poor subjective and objective sleep quality, as well as the anxious and depressive symptoms, are risk factors of chronic pain. Plain Language Summary: This study aimed to understand how common chronic pain is among people with insomnia and what factors might increase the risk of chronic pain in these patients. Insomnia is a sleep disorder where people have trouble falling or staying asleep, and it often occurs alongside other health issues like chronic pain, anxiety, and depression. The researchers studied 358 patients with chronic insomnia from the Sleep Medicine Center at West China Hospital between May 2019 and February 2021. They divided the patients into two groups: those with chronic pain and those without. They used questionnaires to assess sleep quality, mood (anxiety and depression), and pain levels. They also used a special test called polysomnography (PSG) to measure objective sleep quality, which tracks brain activity during sleep. This study found that nearly half (48.9%) of the patients with insomnia also had chronic pain. Patients with chronic pain had higher levels of anxiety and depression, as well as more severe pain. Poor sleep quality, especially shorter deep sleep (known as N3 sleep), was linked to a higher risk of chronic pain. Besides, anxiety and depression were also strongly associated with increased pain intensity. The study suggests that poor sleep quality, especially reduced deep sleep, along with anxiety and depression, may increase the risk of chronic pain in people with insomnia. This means that treating sleep problems and mood disorders could be important for managing chronic pain in these patients. This research show the key point that chronic pain is a major health issue that can significantly affect a person’s quality of life. By understanding the link between insomnia, mood disorders, and chronic pain, doctors can develop better treatment plans that address both sleep and mental health, potentially improving outcomes for patients.Keywords: insomnia, chronic pain, mood disorders, sleep quality